A time-course comparative clinical and immune response evaluation study between the human pathogenic Orientia tsutsugamushi strains: Karp and Gilliam in a rhesus macaque (Macaca mulatta) model. - Manutsanun Inthawong; Piyanate Sunyakumthorn; Sirima Wongwairot; Tippawan Anantatat; Susanna J Dunachie; Rawiwan Im-Erbsin; James W Jones; Carl J Mason; Luis A Lugo; Stuart D Blacksell; Nicholas P J Day; Piengchan Sonthayanon; et al. (Public Library of Science (PLoS), 2022)
Background Scrub typhus is a vector-borne febrile illness caused by Orientia tsutsugamushi transmitted by the bite of Trombiculid mites. O. tsutsugamushi has a high genetic diversity and is increasingly recognized to have a wider global distribution than previously assumed. Methodology/principle findings We evaluated the clinical outcomes and host immune responses of the two most relevant human pathogenic strains of O. tsutsugamushi; Karp (n = 4) and Gilliam (n = 4) in a time-course study over 80 days post infection (dpi) in a standardized scrub typhus non-human primate rhesus macaque model. We observed distinct features in clinical progression and immune response between the two strains; Gilliam-infected macaques developed more pronounced systemic infection characterized by an earlier onset of bacteremia, lymph node enlargement, eschar lesions and higher inflammatory markers during the acute phase of infection, when compared to the Karp strain. C-reactive protein (CRP) plasma levels, interferon gamma (IFN-γ, interleukin-1 receptor antagonist (IL-1ra), IL-15 serum concentrations, CRP/IL10- and IFN-γ/IL-10 ratios correlated positively with bacterial load in blood, implying activation of the innate immune response and preferential development of a T helper-type 1 immune response. The O. tsutsugamushi-specific immune memory responses in cells isolated from skin and lymph nodes at 80 dpi were more markedly elevated in the Gilliam-infected macaques than in the Karp-infected group. The comparative cytokine response dynamics of both strains revealed significant up-regulation of IFN-γ, tumor necrosis factor (TNF), IL-15, IL-6, IL-18, regulatory IL-1ra, IL-10, IL-8 and granulocyte-colony-stimulating factor (G-CSF). These data suggest that the clinical outcomes and host immune responses to scrub typhus could be associated with counter balancing effects of pro- and anti-inflammatory cytokine-mediated responses. Currently, no data on characterized time-course comparisons of O. tsutsugamushi strains regarding measures of disease severity and immune response is available. Our study provides evidence for the strain-specificity of host responses in scrub typhus, which supports our understanding of processes at the initial inoculation site (eschar), systemic disease progression, protective and/or pathogenic host immune mechanisms and cellular immune memory function. Conclusions/significance This study characterised an improved intradermal rhesus macaque challenge model for scrub typhus, whereby the Gilliam strain infection associated with higher disease severity in the rhesus macaque model than the previous Karp strain infection. Difficulties associated with inoculum quantitation for obligate-intracellular bacteria were overcome by using functional inoculum titrations in outbred mice. The Gilliam-based rhesus macaque model provides improved endpoint measurements and contributes towards the identification of correlates of protection for future vaccine development.